Evolution, order, and complexity - Khalil, Elias L., 1957-; Boulding, Kenneth E. (Kenneth Ewart), 1910-1993 (Routledge frontiers of political economy ;, 1996)
Evolution, Order and Complexity reflects topical interest in the relationship between the social and natural worlds. It represents the cutting edge of current thinking which challenges the natural/social dichotomy thesis by showing how the application of ideas which derive from biology can be applied and offer insight into the social realm. This is done by introducing the general system theory to the methodological debate on the relation of human and natural sciences.